Analisis Komparatif Tingkat Pengembalian Value Stocks dan Growth Stocks di Bursa Efek Indonesia - Andre Prasetya Willim (Jurnal Pasar Modal dan Bisnis, 2019)
Purpose- This study aims to examine the difference in returns between portfolio value stocks and growth stocks with comparative analysis. Methods- The population of this research is all companies in the Indonesia Stock Exchange. Based on the results of the purposive sampling method, there were 396 companies that were sampled in this study with IPO criteria before 2011. There were four portfolios formed, namely small growth, small value, big growth and big value portfolios, each consisting of 59 companies. Portfolio performance in this study was measured by the Sharpe, Treynor and Jensen indices. Finding- The results showed a difference in portfolio return value stocks and growth stocks. Return portfolio value stocks are lower than growth stocks portfolios and portfolio performance value stocks are also lower than growth stocks portfolios.